Chronic-phase chronic myeloid leukemia: Not always a reassuring diagnosis. Issue 2 (2015) - Orlandi, Ester M.; Elena, Chiara; Zibellini, Silvia
Abstract: Primary resistance to tyrosine-kinase inhibitors (TKIs) is quite uncommon in chronic-phase Chronic Myeloid Leukemia (CML) and related to still poorly understood mechanisms, as ABL mutations are rarely detected in primary resistant patients. We report the challenging case of a CML patient who was resistant to multiple TKIs because of different emerging ABL mutations and became pregnant while on Nilotinib therapy despite repeated and clear discouragement to conceive. She decided to continue with her pregnancy, showing an admirable and incredible perseverance in the pursuit of her personal aims.